Estudio eléctrico y análisis termográfico de los motores eléctricos y baterías del autobús marca BYD B13S01 del SITP de la ciudad de Bogotá (2022)
For the development of this research, it is intended to analyze through tests thermographic the performance of the electric buses type reference standard B13S01, specifically its synchronous magnet motors and the Silicon-Iron Phosphate battery pack, since these components are a fundamental part of the scaffolding of this technology which to date is being incorporated into the country. The company "E-somos Fontibón" one of the operators in the city of Bogotá, more specifically in the town of Fontibón with a fleet of 126 type electric vehicles standard B13S01, through continuous improvement in its quality management, allows the thermographic analysis for the electric motor and batteries of the buses based on the high cost that these components have in their maintenance plan and in their preservation in the duration of the operation and use of the buses as fundamental assets of its unit of business. In the case of bus operation, there are basically 2 motors electric coupled in the rear axle tires and 16 high-voltage battery packs, for Its acronym in English (HV) High Voltage, these motors are powered by the package of batteries that are connected in series with the cell pack inside and in the configuration external its circuit is of parallel configuration, which in turn are located on the sides bottom of the bus. In the same way, it has a current converter which makes the current distribution from the batteries to the motors or from the motors to the batteries, these components reach high temperatures in their daily work process without 25 be able to visually determine which of these is prone to failure or may be affecting a subsystem. Thermography has allowed maintenance areas in various sectors industrialists determine early intervention actions on high-cost components and that due to their mechanical or electrical functionality are not easy to intervene in their periods inspection [6]. This non-invasive and low-cost technique has guaranteed interventions timely in systems and equipment that depend on constant monitoring, that due to their work constant and high delivered power experience high operating temperatures. This degree work will allow the analysis of the charging curves of the batteries with average storage percentages, taking into account that the company does not have telemetry system or software for installed chargers, data will be collected from vehicles in normal operation arrival and others in a state of inoperative parking